Development plans during Frente Nacional pact in Colombia: the highway to Llano, 1958-1974 - Charry Morales, Ariel (Instituto de Altos Estudios Nacionales IAEN, 2023)
This article determines the importance of the highway to Llano (Bogotá-Villavicencio) in the development plans and public investment during the National Front, the political pact of power alternation of the Liberal and Conservative parties in Colombia between 1958 and 1974. Three national development are reviewed for this purpose: the Economic and Social Development Plan, Development Plans and, and the Four Strategies Program. The layout and reconstruction of the road highlights the discussion on the role of Villavicencio as the most emblematic city/capital of the Llanos, the scope of the regional economy, the impact of internal migration, the absence of national planning and the failed attempt of road modernization. It is concluded that there was a delay in the planning of the road to the Llanos Orientales and little interest in regional issues on the part of the National Front governments.